Minglitan: Chinese Translation and Commentary of Aristotle’s Categories from the 17th Century - Rogacz, Dawid (Peitho. Examina Antiqua, 2016)
This article puts forth the first Polish translation of fragments of Minglitan, „Investigation into the Meaning of Names”, that is Chinese translation and commentary of Aristotle’s Categories prepared by Chinese scholar, Li Zhizao and Portuguese Jesuit, Francisco Furtado, and published in 1631. Five pieces have been select for the translation: Li Tianjing’s preface to Minglitan; a groundbreaking essay on sources of philosophy, containing the very first Chinese transliteration of the term φιλοσοφία; chapter on the category of substance; of quantity; and chapter on opposites. The translation has been furnished with footnotes elaborating on Chinese terms employed in the Minglitan, and has been preceded by an introduction that delineates historical context of Minglitan, its content and structure, along with a brief sketch of its main linguistic determinants.